Numerical simulation of magnetic drug targeting to a tumor in the simplified model of the human lung. (April 2019) - Sabz, M.; Kamali, R.; Ahmadizade, S.
Highlights: The presence of magnetic field, increases DE on tumor surface greatly. The best positions for magnetic source are found under the bifurcations in this study. DE on tumors reduces by enhancement the mass flow rate for I = 10 (A) and I = 15 (A). Abstract: Background: Magnetic drug targeting improves effectiveness of medicine application and reduces its side effects. In this method, drugs with magnetic core are released in the lung and they are steered towards the tumor by applying an external magnetic field. A number of researchers utilized numerical methods to study particle deposition in the lung, but magnetic drug delivery to the tumors in the human lung has not been addressed yet. Method: In the present study, Weibel model is used for human airway geometry from generation G0–G3. Moreover, a tumor is considered in the lung, which is located in G2. Particles are made of iron oxide magnetic cores and poly lactic coglycolic acid shells. Fluid flow is assumed laminar and particles are coupled with the fluid by one-way method. The magnetic field is produced by a coil with law current intensities instead of a wire with high current intensities. Influences of various parameters such as particle diameter, magnetic source position, current intensity, and inlet mass flow rate and tumor size on the deposition efficiency on the tumor surface are reported. Results: Results show that magnetic drug targeting enhances deposition efficiency on the tumor surface Furthermore, when the current intensity rises from 10 (A) to 20 (A), tumor enlarging, and increasing particle diameter, lead to deposition efficiency enhancement, but efficiency decreases by increasing mass flow rate. However, when current intensity is 20 (A), deposition efficiency decreases in two situations. The first situation is when mass flow rate is 7 (L/min) and particle diameter is 9 (µm), and the second one is in 10 (L/min) mass flow rate and 9 (µm) diameter. Conclusion: The results demonstrated that magnetic drug targeting is applicable and suitable for all tumors specially for small tumors ( r / R = 0.5 in this case) that efficiency increase from 0% in the absence of magnetic field to more than 2% in the presence of magnetic field.